2012
DOI: 10.1515/jpem-2012-0274
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism of the osteoprotegerin gene and its association with bone mineral density in Chinese postmenopausal women

Abstract: These findings suggested that g.23276 G>A genotypes in the OPG gene were associated with spine BMD in Chinese postmenopausal women. The A-allele was associated with lower BMD and an increased risk for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…These results suggest that the T allele could be an increased risk for BMD and osteoporosis in Chinese postmenopausal women. Several previous studies have reported associations of many SNPs with BMD and osteoporosis, such as A163G, T245G, T950C, G1181C, G23276A, C21775T, and T23367C, which is consistent with our results that genetic variants of OPG may contribute a genetic influence on osteoporosis and BMD (Arko et al, 2002;Langdahl et al, 2002;Ohmori et al, 2002;Jorgensen et al, 2004;Zhao et al, 2005;Kim et al, 2007;Ueland et al, 2007;Garcia-Unzueta et al, 2008;Moffett et al, 2008;Lee et al, 2010;Feng et al, 2012;Zhang et al, 2013). The g.27667T>A SNP might be linked to other known non-synonymous SNPs influencing the function of the OPG protein, such as lysine (Lys)3asparagine (Asn), isoleucine (Ile)184methionine (Met), and Thr154Met, which have all been shown to be significantly associated with the risk of BMD and osteoporosis (Zhao et al, 2005;Feng et al, 2012;Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that the T allele could be an increased risk for BMD and osteoporosis in Chinese postmenopausal women. Several previous studies have reported associations of many SNPs with BMD and osteoporosis, such as A163G, T245G, T950C, G1181C, G23276A, C21775T, and T23367C, which is consistent with our results that genetic variants of OPG may contribute a genetic influence on osteoporosis and BMD (Arko et al, 2002;Langdahl et al, 2002;Ohmori et al, 2002;Jorgensen et al, 2004;Zhao et al, 2005;Kim et al, 2007;Ueland et al, 2007;Garcia-Unzueta et al, 2008;Moffett et al, 2008;Lee et al, 2010;Feng et al, 2012;Zhang et al, 2013). The g.27667T>A SNP might be linked to other known non-synonymous SNPs influencing the function of the OPG protein, such as lysine (Lys)3asparagine (Asn), isoleucine (Ile)184methionine (Met), and Thr154Met, which have all been shown to be significantly associated with the risk of BMD and osteoporosis (Zhao et al, 2005;Feng et al, 2012;Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The OPG gene is one of the most important candidate genes for BMD and osteoporosis (Pocock et al, 1987;Hofbauer and Schoppet, 2002;Langdahl et al, 2002;Yamada et al, 2003;Arko et al, 2002Arko et al, , 2005Vidal et al, 2011;Feng et al, 2012;Hussien et al, 2013;Zhang et al, 2013). Osteoporosis is a polygenic disease that results from complex interactions between genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a multifactorial disorder characterized by a reduction in bone mineral density (BMD) and a deterioration of bone microarchitecture with a consequent increase of fracture risk (Cummings et al, 1985;Riggs and Melton, 1986;Peck et al, 1993;Kanis et al, 1994;Geng et al, 2007;Garcia-Unzueta et al, 2008;Li et al, 2012;Woo et al, 2012). Genetic factors play important roles in the pathogenesis of primary osteoporosis (Albagha and Ralston, 2006;Ferrari, 2008;Cheung et al, 2010;Hosoi, 2010;Ralston, 2010;Feng et al, 2012;Woo et al, 2012;Zhang et al, 2013). Evidence suggests that low BMD has high heritability.…”
Section: Introductionmentioning
confidence: 99%